Prove:
Using mathemetical induction:
P(n) = [tex]n^{3}+2n+3n^{2}[/tex]
for n=1
P(n) = [tex]1^{3}+2(1)+3(1)^{2}[/tex] = 6
It is divisible by 2 and 3
Now, for n=k, [tex]n > 0[/tex]
P(k) = [tex]k^{3}+2k+3k^{2}[/tex]
Assuming P(k) is divisible by 2 and 3:
Now, for n=k+1:
P(k+1) = [tex](k+1)^{3}+2(k+1)+3(k+1)^{2}[/tex]
P(k+1) = [tex]k^{3}+3k^{2}+3k+1+2k+2+3k^{2}+6k+3[/tex]
P(k+1) = [tex]P(k)+3(k^{2}+3k+2)[/tex]
Since, we assumed that P(k) is divisible by 2 and 3, therefore, P(k+1) is also
divisible by 2 and 3.
Hence, by mathematical induction, P(n) = [tex]n^{3}+2n+3n^{2}[/tex] is divisible by 2 and 3 for all positive integer n.